Aging Effects on Epicardial Adipose Tissue - Iacobellis, Gianluca (Frontiers in Aging, 2021)
Epicardial fat is the visceral fat of the heart. Epicardial fat is a white adipose tissue, but it displays also brown-fat like or beige fat features. Under physiological conditions, epicardial fat has cardioprotective functions such as free fatty acids supply and thermoregulation of the adjacent myocardium. Epicardial adipose tissue encounters changes in the transition from embryological to childhood and then to adult life. Aging can affect the function and morphology of epicardial fat, more likely in women than in men. The effect of aging on the brown fat properties of the epicardial fat is the most prominent and with the greatest clinical implications. It is promising to know that epicardial fat responds to newer pharmaceutical drugs modulating the adipose tissue and potentially restoring its browing effects. Epicardial fat pro-inflammatory secretome is down-regulated in end-stage coronary artery disease. Chronic hypoxia and unfavorable hemodynamic milieu can also affect the regulatory component of the epicardial fat. Epicardial fat may incur in apoptotic and fibrotic changes that alter its transcriptome and proteasome. In conclusion, aging and advanced stage of chronic diseases are likely to influence and affect epicardial fat genes and function. Whether the downregulation of the epicardial fat tissue is due more to aging than advancing stages of coronary artery disease, or more likely to the combination of both, would be object of future investigations.